The mechanics of a graceful exit: Interest on reserves and segmentation in the federal funds market - Morten L. Bech; Elizabeth Klee (Federal Reserve Bank of New York, 2009)
To combat the financial crisis that intensified in the fall of 2008, the Federal Reserve injected a substantial amount of liquidity into the banking system. The resulting increase in reserve balances exerted downward price pressure in the federal funds market, and the effective federal funds rate began to deviate from the target rate set by the Federal Open Market Committee. In response, the Federal Reserve revised its operational framework for implementing monetary policy and began to pay interest on reserve balances in an attempt to provide a floor for the federal funds rate. Nevertheless, following the policy change, the effective federal funds rate remained below not only the target but also the rate paid on reserve balances. We develop a model to explain this phenomenon and use data from the federal funds market to evaluate it empirically. In turn, we show how successful the Federal Reserve may be in raising the federal funds rate even in an environment with substantial reserve balances.
Keywords: E4; E58; G21; G28; 330; Federal funds; segmentation; interest on reserves; corridor system; exit strategy; Geldmarkt; Geldmengensteuerung; Geldpolitisches Ziel; Bankenliquidität; USA